0816 GENDER DIFFERENCES IN OBSTRUCTIVE SLEEP APNEA (OSA) IN PRE-DIABETIC PATIENTS. (28th April 2017) - Siddique, R; Mahmud, I; Cannon, A
Abstract: Introduction: Little is known about gender differences in OSA rates among pre-diabetic patient populations. The purpose of this study was to determine if there was a clinical difference in OSA rates between males and females who had pre-diabetes in a community medical practice. Methods: This study consisted of a total of 65 pre-diabetic patients. According to the American Diabetes Association, pre-diabetes is defined as anyone who has a mean HA1c between 5.7%-6.4%. Patients underwent polysomnography to determine the severity of their OSA. OSA was defined as: mild, moderate or severe based on the Apnea Hypopnea Index (AHI). Mild was classified as AHI of greater than 5 but less than 30 apneas per hour. Moderate was greater than 15 but less than 30 apneas per hour. Severe was defined as over 30 apneas. Males and females were split into two groups where the mean levels of AHI and HA1c were examined based on their respective categories of severity. AHI severity was determined based on two HA1c categories of 5.4 - 6.0 and 6.1 - 6.4. Unpaired t-tests were used to determine significance levels. Results: The percent of females in this study was 57%. The average age of the entire sample was 51 years. The mean HA1c and AHI for males was 5.99 and 33.79 respectively. The mean HA1c and AHI for females was 5.91 and 29.98 respectively (difference of AHI in males v. females=4; p=0.52). Among males, there was a difference of 7 points in AHI between the 5.4–6.0 and 6.1–6.4 HA1c categories (AHI of 31.27 vs. 38.35 respectively). Among females there was an AHI difference of 5 points between the two HA1c categories (AHI of 28.69 vs. 33.49 respectively). The large difference in AHI points between males and females was observed in the 6.1- 6.4 HA1c category (difference=5; p=0.59). Conclusion: There were clinically important differences in OSA between males and females across the entire sample and among different HA1c severity categories. Larger samples sizes will be needed in future studies to confirm and validate the significance of these findings. Support (If Any): Funded by Sleep and Wellness Medical Associates.